Diversity of Bryophytes in Plaosan Temple, Central Java - Ninda Nur Amalia; Heri Sujadmiko (Berkala Ilmiah Biologi, 2022)
Bryophyte grows on various substrates, one of which is rock. Plaosan Temple is composed of andesite stone which has the potential to experience weathering caused by bryophyte. This research aims to determine the diversity of bryophyte, types and classifications of bryophyte, and to determine the bryophyte which are widely and evenly distributed in the rocks of Plaosan Temple, Central Java. Bryophytes samples were collected using the dry herbarium technique and identified at the Plant Systematics Laboratory, Faculty of Biology, UGM. Vegetation analysis was carried out using the quadrat method of 15 x 15 cm plots which were randomly distributed in 52 plots. The environmental parameters measured were air temperature, humidity, and light intensity. Species diversity was analyzed using Shannon-Wiener index. The results obtained 11 types of bryophytes grouped into two classes, namely Hepaticopsida and Bryopsida, including Barbula indica (Hook.) Spreng., Brachymenium exile (Dozy & Molk.) Bosch & Lac., Brachymenium indicum (Dozy & Molk.) Bosch & Lac., Cyathodium smaragdinum Schiffn., Fissidens atroviridis Besch., Fissidens virens Thwait. & Mitt., Fissidens zollingeri Mont., Gymnostomiella vernicosa (Hook.) Fleisch., Hyophila involuta (Hook.) A. Jaeg., Philonotis hastata (Duby) Wijk & Margad., and Riccia hasskarliana Steph. Bryophyte that is widely and evenly distributed is Barbula indica. Keywords: bryophyte; diversity; andesite; Plaosan temple